Microstructural Characterization And Fracture Observation Of Green Innovative Glass (GIG) Ceramic Tiles Produced By Sinter Crystallization Of Waste Glass - Ahmad, Aina Syuhada (2020)
Green Innovative Glass (GIG) Ceramic tile is a ceramic tile that uses waste glass powder arising from municipal wastes. The basic raw material used for fabricating GIG is soda lime silica glass (SLSG) waste which was collected from PUM Cullet SDN BHD. located in Johor Bharu. Most of this cullet were originated from waste glass containers or bottles. It was found that the quality of GIG tiles is of increased mechanical strength compared to the conventional tile in the market. It should be noted that the GIG tile is produced by viscous sintering at lower sintering temperature of 850oC and lower energy than the conventional tile which is produced by solid-state sintering mechanism at higher sintering temperature of commonly 1200oC. Thus, the objective of this work is to characterize the green innovative ceramic (GIG) tile using XRD and SEM, to compare the microstructural properties and fracture behaviour of GIG tiles and unglazed porcelain conventional ceramic tiles and to explain the relation of composition with process and mechanical properties related to the sintering mechanism of GIG tile compared to unglazed porcelain conventional ceramic tile. The microstructural analysis of GIG tile using imageJ, SEM, and XRD is carried out with attention given to its mechanical performance and fracture behaviour. Then, a comparison on the mechanical performance and fracture behaviour related to the crystal phases and microstructural present of GIG and unglazed porcelain conventional ceramic tile is carried out using reported findings via comprehensive literature review. It was found by the imageJ analysis that 0.25%, 0.80% and 0.97% porosity exist in the unglazed porcelain conventional ceramic tile, green GIG and white GIG respectively. The XRD analysis shows that unglazed porcelain conventional ceramic tile consists of Quartz phase while the white and green GIG consists of wollastonite, cristobalite, and fosterite. SEM analysis shows that the fracture behaviour of the unglazed porcelain conventional ceramic tile is having an alignment of crack propagation originated to large grains in the material. While, in the GIG samples cracks propagate more disperse and caused by the microcracks due to transgranular and intergranular fracture. Green GIG shows the deepest crack as it is able to repel lots of stress with less elongation.